Measurements of the decays B0→D̄0pp̄, B0→D̄* 0pp̄, B0→D-pp̄π+, and B0→D*-pp̄π+ - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
We present measurements of branching fractions of B0 decays to multibody final states containing protons, based on 232×106 Υ(4S)→BB̄ decays collected with the BABAR detector at the SLAC PEP-II asymmetric-energy B factory. We measure the branching fractions B(B0→D̄0pp̄)=(1. 13±0.06±0.08)×10-4, B(B0→D̄*0pp̄)=(1. 01±0.10±0.09)×10-4, B(B0→D-pp̄π+)=(3. 38±0.14±0.29)×10-4, and B(B0→D*-pp̄π+)= (4.81±0.22±0.44)×10-4 where the first error is statistical and the second systematic. We present a search for the charmed pentaquark state, Θc(3100) observed by H1 and put limits on the branching fraction B(B0→Θcp̄π+)×B(Θc→D*-p) <14×10-6 and B(B0→Θcp̄π+)×B(Θc→D-p) <9×10-6. Upon investigation of the decay structure of the above four B0 decay modes, we see an enhancement at low pp̄ mass and deviations from phase-space in the D̄p̄ and D̄p invariant mass spectra. © 2006 The American Physical Society.